2019
DOI: 10.1128/mcb.00139-19
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA HOXA-AS3 Integrates NF-κB Signaling To Regulate Endothelium Inflammation

Abstract: The long noncoding RNA HOXA-AS3 has recently been reported to act as a critical regulator in inflammation-linked lung adenocarcinoma. However, the roles of HOXA-AS3 in endothelium inflammation and related vascular disorders remain poorly defined. In the current study, we identified HOXA-AS3 to be a critical activator to promote NF-κB-mediated endothelium inflammation. HOXA-AS3, a chromatin-associated regulator which colocalizes with NF-κB at specific gene promoters, was found to interact with NF-κB and positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…In the current study, we identified a novel lncRNA, HOXA cluster antisense RNA 3 (HOXA‐AS3). It was found to be one of the most up‐regulated lncRNAs in GBM tissues 10,11 . HOXA‐AS3 is a HOX cluster, and it is a set of transcription factor genes that regulate hematopoietic lineage differentiation and embryological development 10,12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we identified a novel lncRNA, HOXA cluster antisense RNA 3 (HOXA‐AS3). It was found to be one of the most up‐regulated lncRNAs in GBM tissues 10,11 . HOXA‐AS3 is a HOX cluster, and it is a set of transcription factor genes that regulate hematopoietic lineage differentiation and embryological development 10,12 .…”
Section: Introductionmentioning
confidence: 99%
“…It was found to be one of the most up-regulated lncRNAs in GBM tissues. 10,11 HOXA-AS3 is a HOX cluster, and it is a set of transcription factor genes that regulate hematopoietic lineage differentiation and embryological development. 10,12 Members of the HOX cluster family, such as HOXA-AS2, have been shown to regulate cell proliferation and the formation of tumour-related vasculogenic mimicry in various tumours.…”
mentioning
confidence: 99%
“…All of the 39 Hox genes are classified into four clusters, namely HoxA, HoxB, HoxC, HoxD respectively (Bhatlekar et al, 2014). Among the four clusters, HoxA cluster has attracted increasing attention because of its critical regulatory role in development of cardiovascular diseases, such as cardiac morphogenesis, ventricular septal defects, and endothelial inflammation (Di-Poi et al, 2010;Zhu et al, 2019a;Zhu et al, 2019b;Beachy et al, 2013;Makki and Capecchi, 2012). Recent studies have revealed that HoxA9, a member of HoxA cluster genes, was downregulated in hypertensive patients (Pirro et al, 2007), and that mRNA level of HoxA9 was enhanced in cardiac hypertrophy (Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB signaling is a central mediator of GC progression [25]. HOXA-AS3 is able to colocalize with NF-κB in the promoter region of certain genes, and can directly interact with this transcription factor in order to enhance its activation by regulating IκBα expression and p65 subunit K310 acetylation status [17]. As such, we speculated that HOX-AS3 may drive GC progression via the activation of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, HOXA-AS3 has been shown to positively regulate NF-κB signaling by interacting with this transcription factor [17], and abnormal NF-κB signaling can promote GC progression [18][19][20]. As such, we evaluated the ability of HOXA-AS3 to modulate NF-κB signaling in our GC model system.…”
Section: Hoxa-as3 Modulates Nf-κb Signaling To Regulate Gc Cell Biologymentioning
confidence: 97%